Analysis of differences in the transcriptomic profiles of eutopic and ectopic endometriums in women with ovarian endometriosis - Xiao Feng; Lingbin Qi; Xiaoyu Xu; Yun Feng; Xiaoming Gong; Aixingzi Aili; Yu Chen; Zhigang Xue; Jinfeng Xue; Xiaowen Tong (PeerJ, 2021)
Background Endometriosis is a common gynecological disease among women in their reproductive years. Although much effort has been made, the pathogenesis of this disease and the detailed differences between eutopic endometrial cells and ectopic endometrial cells are still unclear. Methods In this study, eutopic and ectopic endometrial cells were collected from patients with and without endometriosis and RNA sequencing was performed. The gene expression patterns and differentially expressed genes (DEGs) in eutopic and ectopic endometrial cells, as well as control endometrial cells, were analyzed using a weighted gene co-expression network analysis (WGCNA) and the DESeq2 package. The functions of significant genes were detected using Gene ontology (GO) enrichment analysis, and qRT-PCR validation was performed. Results The results indicated that eight gene modules were found among these three groups. They also indicated that the gene module, which is highly related to eutopic endometrial cells, was mainly enriched in cell adhesion, embryo implantation, etc., while the gene module related to ectopic endometrial cells was mainly enriched in cell migration, etc. The results of differential expression analysis were generally consistent with the WGCNA results through identified significant DEGs between different groups. These DEGs may play an important role in the occurrence of endometriosis, including the infertility associated gene ARNTL and PIWIL2, tissue remodeling gene MMP11, cell survival and migration gene FLT1, inflammatory response gene GNLY, the tumor suppressor genes PLCD1, etc. Further analysis suggested the function of adhesion is stronger in ectopic endometrial cells than in eutopic endometrial cells, while the ectopic endometrium may have a higher potential risk of malignant transformation than eutopic endometrium. Conclusions Overall, these data provide a reference for understanding the pathogenesis of endometriosis and its relationship with malignant transformation.